2019
DOI: 10.3389/fmicb.2019.02106
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting Plant Growth-Promoting Rhizobacteria That Mitigate Drought Stress in Grasses

Abstract: This study reports the application of a novel bioprospecting procedure designed to screen plant growth-promoting rhizobacteria (PGPR) capable of rapidly colonizing the rhizosphere and mitigating drought stress in multiple hosts. Two PGPR strains were isolated by this bioprospecting screening assay and identified as Bacillus sp. (12D6) and Enterobacter sp. (16i). When inoculated into the rhizospheres of wheat (Triticum aestivum) and maize (Zea mays) seedlings, these PGPR resulted in delays in the onset of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(103 citation statements)
references
References 53 publications
3
94
0
6
Order By: Relevance
“…Among them, 13 strains (61.9%) were identified as Pseudomonas comprising 8 species [P. fluorescens (ESR7 and ESR25), P. azotoformans (ESR4), P. chlororaphis (ESR3 and ESR15), P. poae (ESR6), P. gessardii (ESR9), P. cedrina (ESR12, ESR16, and ESR23), P. veronii (ESR13 and ESR21), and P. parafulva ESB18] and 6 strains (28.6%) were Bacillus with 4 species [B. cereus (ESD3, ESD21, and ESB22), B. horikoshii (ESD16), B. aryabhattai (ESB6), and B. megaterium (ESB9)] ( Table 1). Pseudomonas and Bacillus are well-known plant-growth promoters (Kumar et al, 2012;Backer et al, 2018;Chandra et al, 2018;Naseem et al, 2018;Jochum et al, 2019). Among the identified rhizobacteria, B. cereus (Yan et al, 2017), P. chlororaphis (Selin et al, 2010), and P. fluorescens (Ude et al, 2006) were only reported to form biofilms under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 13 strains (61.9%) were identified as Pseudomonas comprising 8 species [P. fluorescens (ESR7 and ESR25), P. azotoformans (ESR4), P. chlororaphis (ESR3 and ESR15), P. poae (ESR6), P. gessardii (ESR9), P. cedrina (ESR12, ESR16, and ESR23), P. veronii (ESR13 and ESR21), and P. parafulva ESB18] and 6 strains (28.6%) were Bacillus with 4 species [B. cereus (ESD3, ESD21, and ESB22), B. horikoshii (ESD16), B. aryabhattai (ESB6), and B. megaterium (ESB9)] ( Table 1). Pseudomonas and Bacillus are well-known plant-growth promoters (Kumar et al, 2012;Backer et al, 2018;Chandra et al, 2018;Naseem et al, 2018;Jochum et al, 2019). Among the identified rhizobacteria, B. cereus (Yan et al, 2017), P. chlororaphis (Selin et al, 2010), and P. fluorescens (Ude et al, 2006) were only reported to form biofilms under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…When required, the pots were transferred in the rain shelter. The pot was watered with sterile deionized water to field capacity [when water was leached through bottom holes of the pots, this was considered maximum field capacity (Chandra et al, 2018;Jochum et al, 2019)] every day up to 45 days post planting (DPP). In order to impose water stress, the soil in the root region of each plant was carefully loosened.…”
Section: Root Bacterization Seedling Transplantation and Imposing Wmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that PGPR belonging to different genera and host plants are capable to alleviate abiotic stresses in plants by augmenting their defense system ( Amna et al, 2020 ; Jochum et al, 2019 ; Yasmin et al, 2017 ). Similarly, the application of SA enhances tolerance to drought stress, thereby not only mitigating the damaging effects of drought stress but also enhancing its tolerance ( Khan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…agropec. pernamb., Recife,25(2), e2282252020, 2020 fixação de nitrogênio atmosférico CEREZINI;IKEDA et al, 2020;MAHMUD et al, 2020;MORETTI et al, 2020); atua na produção de sideróforos (ZAREI et al, 2019;KOUR et al, 2020;PURI;PADDA;CHANWAY, 2020;TORRES et al, 2020); redução do efeito de estresse oxidativo (FUKAMI et al, 2018;SARKAR et al, 2018;HARMAN;UPHOFF, 2019;JOCHUM et al, 2019;YOOLONG et al, 2019); e como controle biológico e redutor do efeito de fitopatógenos (STURZ;NOWAK, 2000;TIAN;YANG;ZHANG, 2007;VERMA;WHITE, 2018).…”
Section: Introductionunclassified